1986
DOI: 10.1246/bcsj.59.781
|View full text |Cite
|
Sign up to set email alerts
|

On the Mechanism of Transfer of Sodium Ion across the Nitrobenzene/Water Interface Facilitated by Dibenzo-18-crown-6

Abstract: The question of the site of ionophore–ion complex formation, whether it is in the organic phase (EC), in the aqueous phase (CE), or at the interface (E), in the transfer facilitated by dibenzo-18-crown-6 of sodium ion across the nitrobenzene/water interface was studied by kinetic analysis of the ion transfer using a.c. polarographic method. The results indicate that the interface reaction mechanism (E) is the most probable of the three.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
35
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(40 citation statements)
references
References 18 publications
5
35
0
Order By: Relevance
“…Senda et al 96 studied the transfer of sodium at the water-nitrobenzene interface facilitated by dibenzo-18-crown-6 in order to elucidate the mechanism of the transfer, and concluded that the transfer occured by a TIC mechanism. Recently, Shao 73 revisited this system at the water-1,2-dichloroethane interface.…”
Section: Facilitated Ion Transfermentioning
confidence: 99%
“…Senda et al 96 studied the transfer of sodium at the water-nitrobenzene interface facilitated by dibenzo-18-crown-6 in order to elucidate the mechanism of the transfer, and concluded that the transfer occured by a TIC mechanism. Recently, Shao 73 revisited this system at the water-1,2-dichloroethane interface.…”
Section: Facilitated Ion Transfermentioning
confidence: 99%
“…Vanýsek et al [52] demonstrated that the K + transfer facilitated by valinomycin from W to NB takes place both through complex formation in NB or in parallel at the interface. Lin and Freiser [53] reported that the mechanism of K + transfer facilitated by DB18C6 at the W/DCE interface depended on the concentration of K + in W. Kakutani et al [54] studied Na + transfer facilitated by DB18C6 by means of a.c. polarography at the W/NB interface, and concluded that complex formation at the interface was the most probable mechanism.…”
Section: Crown Ethers and Valinomycinmentioning
confidence: 99%
“…Depending on the different concentration ratios, different types of ion transfer reactions can be envisaged [33,34].…”
Section: Assisted Ion Transfermentioning
confidence: 99%